Performance of All-Optical XNOR Gate Based on Two-Photon Absorption in Semiconductor Optical Amplifiers. (31st December 2014) - Kotb, Amer
Abstract : All-optical logic XNOR gate is realized by a series combination of XOR and INVERT gates. This Boolean function is realized by using Mach-Zehnder interferometers (MZIs) and exploiting the nonlinear effect of two-photon absorption (TPA) in semiconductor optical amplifiers (SOAs). The employed model takes into account the impact of amplified spontaneous emission (ASE), input pulse energy, pulsewidth, SOAs carrier lifetime, and linewidth enhancement factor ( α -factor) on the gate's output quality factor ( Q -factor). The outcome of this study shows that the all-optical XNOR gate is indeed feasible with the proposed scheme at 250 Gb/s with both logical correctness and acceptable quality.